2009
DOI: 10.1111/j.1399-3054.2008.01182.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and substrate specificities of desulfo‐glucosinolate sulfotransferases in Arabidopsis thaliana

Abstract: Sulfotransferases (SOTs) (EC 2.8.2.-) catalyze the transfer of a sulfate group from the cosubstrate 3'-phosphoadenosine 5'-phosphosulfate (PAPS) to a hydroxyl group of different substrates. In Arabidopsis thaliana, three SOTs were identified to catalyze the last step of glucosinolate (Gl) core structure biosynthesis called AtSOT16, 17 and 18. These enzymes from Arabidopsis ecotype C24 were overexpressed in Escherichia coli and purified by affinity chromatography. Recombinant proteins were used to determine sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…BnSOT17-a preferred long-chained methionine-derived ds-Gls 4MTB and 5MTP. These results correspond with the substrate specificities to the AtSOT homologs (Klein and Papenbrock, 2009). Therefore, knowledge about AtSOT16 and AtSOT17 could generally be transferred to Brassica species.…”
Section: The Bnsots Analyzed Have Similar Substrate Specificities As supporting
confidence: 80%
See 4 more Smart Citations
“…BnSOT17-a preferred long-chained methionine-derived ds-Gls 4MTB and 5MTP. These results correspond with the substrate specificities to the AtSOT homologs (Klein and Papenbrock, 2009). Therefore, knowledge about AtSOT16 and AtSOT17 could generally be transferred to Brassica species.…”
Section: The Bnsots Analyzed Have Similar Substrate Specificities As supporting
confidence: 80%
“…The preferences of AtSOT17 and 18 are long chained aliphatic methylthio Gls, such as ds-7-methylthioheptyl Gl and ds-8-methylthiooctyl Gl (Klein et al, 2006;Klein and Papenbrock, 2009;Piotrowski et al, 2004). Detailed analysis of AtSOT18 from different ecotypes showed that the exchange of only one or two amino acids can lead to different affinities to the substrate and PAPS (Klein et al, 2006;Klein and Papenbrock, 2009;Luczak et al, 2013). The questions remain, whether AtSOT16 to 18 are specific for A. thaliana, or if there are homologous SOTs in other Glsynthesizing plants.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations